Study of vietnamese Rhinoceros (Rhinoceros sondaicus annamiticus) food plants in the Cat Tien national park, Vietnam - Dang, Nguyen Xuan; Tue, Ha Van (Academia Journal of Biology, 2014)
The study of vietnamese rhinoceros (Rhinoceros sondaicus annamiticus) food plants was conducted in Catloc sector of the Cattien national park, where the last population of this sub-species survived. The study was based on the analysis of 13 fresh rhino dung piles and specimens collected from plants eaten by the rhinos during 1999 to 2004. 68 rhino food plant species were identified; most of them are wood trees and bushes, except 3 herb species. 14 species are ‘very favorite”, 37 species are “favorite” and 17 species are “accidental” rhino food plants. The forests in Catloc are mainly mixed bamboo-wood forests and regenerating small bamboo forests that contain low density of rhino food plants. These rhino food plants are affected by the human harvest, the destruction and the forage of other great ungulates (gaur, sambar deer, barking deer etc.) in the area.